2020
DOI: 10.1002/htj.22018
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for the computation of systems containing different types of integral and integro‐differential equations

Abstract: An easy and efficient technique is applied to get a reliable analytic approximate solution of linear and nonlinear integral and integro‐differential equations arising in the phenomena of everyday life. The proposed technique consists of a series only in which the unknown constants are determined in the usual way. The obtained results by this technique are in good agreement with the exact solution and it is proved that this technique is effective and easy to apply. Some problems are solved to prove the above cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The suggested method comprises solely of a series in which the undefined constants are found in the conventional manner. The results achieved using the method are in good agreement with the exact solution, demonstrating that it both effective and simple to use [4]. The Lyapunov's functional technique is used to conduct new research on the stability, asymptotically stability and instability of the zero solution, boundedness, integrability of solutions and integrability of derivatives of solutions of certain nonlinear (DIDEs).…”
Section: Introductionmentioning
confidence: 66%
“…The suggested method comprises solely of a series in which the undefined constants are found in the conventional manner. The results achieved using the method are in good agreement with the exact solution, demonstrating that it both effective and simple to use [4]. The Lyapunov's functional technique is used to conduct new research on the stability, asymptotically stability and instability of the zero solution, boundedness, integrability of solutions and integrability of derivatives of solutions of certain nonlinear (DIDEs).…”
Section: Introductionmentioning
confidence: 66%
“…4 are predefined sufficiently small constants for the 1-st iteration. By solving the SOS-based stability condition in (20) to (25), we can obtain the solution for the 2-nd iteration: X (2) (x(t)) and N (2) (x(t)). Also, G (2) (x(t)) = N (2) (x(t))X (2) (x(t)) −1 .…”
Section: Iterative Stability Analysismentioning
confidence: 99%
“…The research works focus on the domains of attraction for polynomial nonlinear systems were reported in [8,9] Also the approaches in [10][11][12][13][14][15][16][17][18] adopted polynomial terms in the fuzzy-model-based (FMB) control. It is worth mentioning that the SOSbased techniques also have the potential to be applied to solve the dynamic problems in the heat transfer investigation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The present article investigates bioconvection Casson nanoliquid film sprayed on a stretching cylinder in the presence of homogeneous-heterogeneous chemical reactions using HAM solution [60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%